A randomised controlled trial of benefit finding in caregivers: The Building Resources in Caregivers Study Protocol. Issue 2 (7th July 2015) - Brand, Charles; O'Connell, Brenda H; Gallagher, Stephen
Caregivers may engage in benefit finding, that is, an increase in perceived positive growth, as a cognitive strategy for coping with stress. The Building Resources in Caregivers study will compare effects of a brief benefit finding writing intervention with a control intervention. Caregivers of people with mental and physical disabilities will be randomised into either a benefit-writing group or a neutral writing group. Caregivers will complete measures relating to themselves and care-recipients (e.g. sociodemographics and illness type) and psychometric measures of benefit finding, distress and quality of life at three time points. Additionally, qualitative commentary on participation experiences will be gathered.